2021
DOI: 10.1371/journal.ppat.1009491
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial epithelial DNA methyltransferase 3b dampens pulmonary immune responses during Pseudomonas aeruginosa infection

Abstract: DNA methyltransferase (Dnmt)3b mediates de novo DNA methylation and modulation of Dnmt3b in respiratory epithelial cells has been shown to affect the expression of multiple genes. Respiratory epithelial cells provide a first line of defense against pulmonary pathogens and play a crucial role in the immune response during pneumonia caused by Pseudomonas (P.) aeruginosa, a gram-negative bacterium that expresses flagellin as an important virulence factor. We here sought to determine the role of Dntm3b in respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Next, we quantified 5-methylcytosine (5-mC) levels in monocytes obtained from a subset of CAP patients ( n =21), captured during the acute disease stage, as well as control participants ( n =16) by methylated DNA immunoprecipitation (MeDIP) [ 41 ]. The characteristics of CAP patients and controls are tabulated in Additional file 3 : Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we quantified 5-methylcytosine (5-mC) levels in monocytes obtained from a subset of CAP patients ( n =21), captured during the acute disease stage, as well as control participants ( n =16) by methylated DNA immunoprecipitation (MeDIP) [ 41 ]. The characteristics of CAP patients and controls are tabulated in Additional file 3 : Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Lung inflammation is determined by pathology analysis and by measurement of myeloperoxidase and elastase levels in lung homogenates using ELISA. In BALF, leukocyte influx is determined using flow cytometry (Qin et al, 2020 and2021a). The epithelial cell responses are evaluated by measuring mRNA levels of inflammatory genes (relative to a housekeeping gene) in lung brushes using RT-qPCR analysis (Qin et al, 2020(Qin et al, , 2021a(Qin et al, and 2021b.…”
Section: Discussionmentioning
confidence: 99%
“…by measuring bacterial burden, inflammatory cytokine production, and pathological changes in both lung and distal organs. Procedure A is also applicable to study lung immune responses or inflammation induced by intranasal inoculation of Methicillin-resistant Staphylococcus aureus (Meijer et al, 2021), or bacterial compounds, such as flagellin (Qin et al, 2021b) and lipopolysaccharide (Otto et al, 2020). according to formula: final volume (mL)= 10 × OD620/0.5.…”
mentioning
confidence: 99%
“…DNA methylation enzymes are important for regulating host immune responses against this bacterium infection, as indicated by the association between genetic variants of DNMT3B and P. aeruginosa infection in children ( 168 ). We recently identified a role for DNMT3B in bronchial epithelial cells during P. aeruginosa pneumonia ( 169 ). DNMT3B deficient human bronchial epithelial cells produced more CXCL1 and related chemokines than control cells when stimulated with P. aeruginosa .…”
Section: Modification Of Dna Methylation Associated With Infectionmentioning
confidence: 99%
“…These in vitro findings were corroborated by studies in mice with bronchial epithelial Dntm3b deficiency infected with viable P. aeruginosa via the airways, which showed increased Cxcl1 expression in bronchial epithelium and CXCL1 protein release together with enhanced neutrophil recruitment and accelerated bacterial clearance. Additional studies using purified flagellin (an important virulent factor expressed by Pseudomonas ) and a flagellin-deficient P. aeruginosa strain demonstrated that bronchial epithelial DNMT3b impaired host defense during Pseudomonas induced pneumonia at least in part by diminishing mucosal responses to flagellin ( 169 ). In separate investigations we showed that the DNA methylation eraser TET2 maintains epithelium barrier function during acute P. aeruginosa infection in mice ( 204 ).…”
Section: Modification Of Dna Methylation Associated With Infectionmentioning
confidence: 99%